Salt stress alleviation by seed priming with silicon in lettuce seedlings: an approach based on enhancing antioxidant responses - Alves, Rita de Cassia [UNESP]; Malvas Nicolau, Mayara Cristina [UNESP]; Checchio, Mirela Vantini [UNESP]; Sousa Junior, Gilmar da Silveira [UNESP]; Oliveira, Francisco de Assis de; Prado, Renato Melo [UNESP]; Gratao, Priscila Lupino [UNESP] (Inst Agronomico, 2020)
Seed germination and seedling growth are the stages most sensitive to salt stress, which can induceion-specific effects and oxidative stress. Although silicon (Si)has been known to improve plant defense systems against stressful-conditions, little is known about seed-priming with Si and mechanisms-of Si-mediated alleviation of salt stress in seedlings. To further the modulation of salt-stress responses and their relation with Si, seed priming with calcium silicate(0, 0.05 and 0.1mM Ca2SiO4) was used in lettuce seeds to improve seed germination and tolerance on subsequent salt-stress exposure (0 and 50 mM NaCl). The effect of Si-priming was assessed on germination, germination rate index and mean germination time and survival of seedlings in salt-stressful conditions supported by biochemical approach involving antioxidant responses. Overall results indicated that Si plays a role in alleviating the negative effects of salt stress by improving germination performance and displayed increased SOD, CAT and GR activities and reduced malondialdehyde and H2O2 contents. Thus,our findings demonstrate that seed-priming with Si is an efficient management technique that can be used to alleviate deleterious effects of salt-stressful on germination of lettuce seeds and enhance salt tolerance of seedlings due the increased activity of ROS-scavenging enzymes.
Keywords: antioxidant enzymes; Lactuca sativa; oxidative damages; salinity